Sustainable consumption and production: a conceptual framework and agenda for research. (6th July 2020) - Moyo, Theresa; Ngwakwe, Collins C.
This paper presents a novel multidimensional conceptual framework for achieving sustainable consumption and production. The paper adopts a qualitative approach through literature and theoretical reviews. The paper argues that while current research on SCP is dominated by a market-oriented philosophical configuration, the quest for sustainability has to integrate non-market considerations, which drives consumerism. After exploring the theoretical dimensions and the literature review, the paper leans on these to develop a new framework, which this paper refers to as 'multidimensional framework for sustainable consumption and production'; this is followed by a proposal of five new research models for further researching of sustainable sourcing of materials, sustainable production, sustainable consumption, sustainable distribution and sustainable waste management. The suggested framework and the five models provide new insight for improved policy and practice. This paper contributes new framework and models, which is absent in the literature.